1986
DOI: 10.1002/j.1939-4640.1986.tb00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Sperm Density Profiles Following 16‐Week Therapy with Continuous Infusion of High‐dose LHRH Analog Plus Testosterone

Abstract: LHRH agonist analogs have been investigated as potential male contraceptives. It has been shown that the LHRH agonistic analog [D-Trp6,Pro9-NEt] LHRH (LHRHA) given to men in single doses up to 500 micrograms daily for up to 20 weeks with the coadministration of testosterone enanthate produces reversible oligozoospermia. Individual responses to the treatment, however, were variable. In this study, we gave the same analog to eight normal male volunteers as a continuous infusion of 500 micrograms daily for 16 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…5) [24], This 'es cape' phenomenon did not appear to be re lated to an insufficient dose of GnRH-A since a similar effect was observed in men receiving either 1 or 10 mg of D-Leu6-GnRH proethylamidc daily. A recent study by Pavlou et al [28] demonstrated a similar FSH escape in normal men receiving 500 pg daily of D-Trp-GnRH proethylamide by subcuta neous infusion over a 12-week period ( fig. 8).…”
Section: Hormonal Data In Patients Treated With Gnrh Agonistsmentioning
confidence: 94%
“…5) [24], This 'es cape' phenomenon did not appear to be re lated to an insufficient dose of GnRH-A since a similar effect was observed in men receiving either 1 or 10 mg of D-Leu6-GnRH proethylamidc daily. A recent study by Pavlou et al [28] demonstrated a similar FSH escape in normal men receiving 500 pg daily of D-Trp-GnRH proethylamide by subcuta neous infusion over a 12-week period ( fig. 8).…”
Section: Hormonal Data In Patients Treated With Gnrh Agonistsmentioning
confidence: 94%
“…In rats, dogs, non human primates, they are able to produce reversible azoospermia [7]. In the latter spe cies, T can prevent azoospermia if adminis tered before the first month of therapy with the agonist [7], In men, it has been shown that LHRH agonists administered either subcutaneously or as continuous infusion up to 500 pg day for 20 weeks could induce low sperm counts with variable individual re sponses [5]. Azoospermia has been obtained only on rare occasions.…”
Section: Discussionmentioning
confidence: 99%
“…Further azoospermia is not always stable whenever it has been ob tained. GnRH agonists achieve complete FSH and bioLH suppression by desensitiza tion of gonadotropic cells at the pituitary level [2], Since the initial study of Bergquist et al [3] in 1979, many trials have been performed using either LHRH alone for a short period of time or in association with T. More recently, several trials in men used large doses of LHRH agonists (up to 500 pg) administered subcutaneously or as con tinuous subcutaneous infusion [4,5], These trials did not produce azoospermia and re sulted only in a 83% decrease in overall sperm counts. In order to investigate the effect of long-term therapy with GnRH ago nist in men, we studied the effects of a depot preparation of D-Trp6 GnRH in 10 normal men for at least 30 weeks.…”
mentioning
confidence: 99%
“…GnRH agonists are known to inhibit FSH and LH secretion after a more or less pro¬ longed period of time during which hyperstimulation of gonadotropins may lead to a flair up of disease symptoms (1)(2)(3). Furthermore, inhibition of spermatogenesis obtained with GnRH agonists in male subjects is incomplete (4,5). By contrast, GnRH antagonists, which directly inhibit gonado¬ tropin secretion without an initial period of stim¬ ulation, appear to be a better alternative.…”
mentioning
confidence: 86%
“…In order to study the kinetics of the effect of ORG 30850 ANT on the release of GnRH-induced gonadotro¬ pin, a 24-h pre-incubation without GnRH and GnRH an¬ tagonist was carried out followed by incubations with 10~8 mol/1 GnRH lasting either 1, 2, 3, 4, 5, or 6 h. ORG 30850 ANT was used at molar concentrations of 0, 10~12, 10~10, and 10"8. 4. The influence of progressive stimulation by GnRH was investigated in the presence of three constant doses of ORG 30850 ANT (10~8 mol/1, 10~9 mol/1, and 10"'°m ol/1).…”
Section: Assaysmentioning
confidence: 99%